Penerapan Metode Fuzzy Simple Additive Weighting (SAW) untuk Menentukan Peningkatan Hasil Belajar Siswa Paling Baik - Dedy Mulyadi (Teknois : Jurnal Ilmiah Teknologi Informasi dan Sains, 2021)
Student learning outcomes are the results obtained by students after the student has carried out learning and learning activities accompanied by evidence of success that has been achieved by a student by involving cognitive, affective, and psychomotor aspects expressed in the form of symbols, letters, and sentences. One of the wishes of the classroom teacher is to find out which students have increased from the learning and learning outcomes that have been carried out in school, but have difficulty making decisions in determining which students have experienced the best increase in learning outcomes. The Fuzzy Simple Additive Weighting (F-SAW) method is suitable for use as a decision support system to help teachers decide which students with the best improvement in learning outcomes.